THE IMPACT OF EXCHANGE RATES ON THE MEASUREMENT AND ACCOUNTING DISCLOSURE IN THE FINANCIAL STATEMENTS IN COMMERCIAL BANKS IN JORDAN - Bani At, Haider Mohammed Ali (European Scientific Journal, ESJ, 2014)
The research aims to clarify the effect of exchange rates on the measurement and accounting disclosure in the financial statements in commercial banks in Jordan and the commitment of the commercial banks listed on the Amman Financial Market in Jordan to disclose the accounting on the translation differences foreign exchange earnings and the statement of the impact of changes in currency exchange rates on the elements of financial statements and also calls for IAS 21: the effects of changes in exchange rates and to identify the relationship between the changes of exchange rates and the elements of financial statements. To achieve the objectives of the study, the researcher used the descriptive method, analytical and interpretative as well as analysis of variance and display graphics, tables, illustrations to clarify the relationships between the variables of the study . The study found that the banks of Jordan is committed to applying the requirements of International Accounting Standard (No. 21): the effects of changes in exchange rates, for each of the translation of transactions denominated in foreign currencies and net investments in foreign subsidiaries and foreign operations which are complementary to the Bank’s operations and the translation of vocabulary of the financial statements of foreign affiliates of the Bank, and disclosure requirements of the standard, showing results of the analysis study it. There is also a relationship between each of the earnings per share in commercial banks operating in Jordan and the volume of assets in commercial banks and shareholders equity and cash flows and profits of commercial banks and changes in exchange rates and are affected by. The researcher recommended the need to adhere to the application of IAS 21: the effects of changes in exchange rates and the rest of the criteria because of its importance is reflected on the financial statements and thus the resolution used in the decision-making banks and auditing firms to keep up with new developments in international standards, to take by changes in the the terms of the criteria for modernization, development and activating the role of financial statements in making rational decision, the need to do studies take into account the effects of changes in exchange rates on the financial statements in whole or in part, as well as the need for further studies that take into account the commitment of the Jordanian banks apply other standard.